2016
DOI: 10.1002/jcp.25361
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated E2F5/p38/SMAD3 Circuitry Reinforces the Pro-Tumorigenic Switch of TGFβ Signaling in Prostate Cancer

Abstract: Transforming growth factor-β signaling exerts divergent effects on normal and cancer cells, although mechanism underlying this differential behavior remains unclear. In this study, expression of 94 genes pertaining to the TGF-β signaling pathway was compared between tumor and benign tissue samples from the human prostate gland to identify major discriminators driving prostate carcinogenesis. E2F5 was identified as one of the most deregulated genes in prostate cancer tissues, predominantly in samples with Gleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…Cells were passaged regularly when they reached 80–85% confluency. Cells were detached by standard trypsinization with Trypsin-EDTA solution 47 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were passaged regularly when they reached 80–85% confluency. Cells were detached by standard trypsinization with Trypsin-EDTA solution 47 .…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear-emitted fluorescence was measured with a BD FACSVerse TM (BD Biosciences). 10,000 events were analyzed from each run 47 . The percentages of cells distributed in the G 1 , S, G 2 /M and sub-G 1 phases of the cell cycle were determined by analysis with the BD FACSuite™ software, version 1.0.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a multifunctional cytokine, transforming growth factor-β (TGF-β) plays a certain role in cells in autocrine and paracrine manner. Smad3 is an important member of the Smad protein family and a major component of TGF-β/Smad signaling pathway (18,19). We regulated the expression level of Smad3 and found that the downregulation of the expression level significantly inhibited the proliferation and invasion of prostate cancer cells, but significantly increased the apoptotic rate of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…E2F4 were overexpressed in PCa epithelial cells [24], and regulated cell cycle by forming complexes with P130 [25]. E2F5 overexpression induced uncontrolled cellular proliferation by up-regulating phosphorylation of SMAD3 and p38 in PCa [26]. The endogenous SMAD2/3 interacted with PKCε to cause SMAD3 to bind to the promoter of glycolysis genes, induced the expression of glycolysis genes HIF-1α, HKII, PFKP and MCT4 and promoted aerobic glycolysis, thereby promoting PCa cell proliferation [27].…”
Section: Discussionmentioning
confidence: 99%